SATPOL PP Performance Assessment Using the WASPAS Method in Decision Making Effectiveness - Lutfiah, Siti; Priyatna, Bayu; Hananto, April Lia; Novalia, Elfina (STMIK Budi Darma, 2024)
Civil Service Police Unit (SATPOLPP) as one of the government's instruments enforces regional regulations and maintains security and protects the community. Leaders have difficulties when evaluating the performance of their members. Manual performance measurement is very ineffective if carried out randomly or by self-assessment. Performance assessments in local government must follow the procedures or rules applicable in local government regulations. Apart from that, the standard for evaluating honorary staff must be based on assessment criteria. In carrying out the analysis, an effective system is needed that can assess the results of member performance. So a performance assessment decision support system is needed using the Weighted Aggregated Sum Product Assessment (WASPAS) algorithm. The WASPAS method has the ability to solve multi-criteria decision problems which are able to reduce errors and optimize in providing assessments and determining alternative highest and lowest values, speed in data management and provide information output results in the form of reports containing performance assessment ranking results. The weights for each criterion are Absence (20%), Work (40%), Collaboration (10%), Discipline (10%), and Knowledge (20%). The results of manual calculations and the application of the WASPAS method show that the highest alternative value obtained a value of 50.5 to the lowest alternative which obtained a value of 26.5 with the same accuracy. so that the evaluation and sanctions obtained can decide who gets ownership and which members can be recommended to extend the work contract using the criteria for consideration. With this calculation system, it becomes faster and more effective in obtaining performance scores for SATPOLPP members and speeding up the leadership decision-making process.